Health systems research in a low-income country: easier said than done. - English, M; Irimu, G; Wamae, A; Were, F; Wasunna, A; Fegan, G; Peshu, N (2008)
Small hospitals sit at the apex of the pyramid of primary care in the health systems of many low-income countries. If the Millennium Development Goal for child survival is to be achieved, hospital care for referred severely ill children will need to be improved considerably in parallel with primary care in many countries. Yet little is known about how to achieve this. This article describes the evolution and final design of an intervention study that is attempting to improve hospital care for children in Kenyan district hospitals. It illustrates many of the difficulties involved in reconciling epidemiological rigour and feasibility in studies at a health system, rather than an individual, level and the importance of the depth and breadth of analysis when trying to provide a plausible answer to the question: does it work? Although there are increasing calls for more health systems research in low-income countries, the importance of strong, broadly based local partnerships and long-term commitment even to initiate projects is not always appreciated.